Financial Sector and its Role and Activities within International Tax Planning - Jedlička, Vít; Jedlička, Pavel (Univerzita Hradec Králové, 2018)
This contribution monitors position of banks in international tax planning. From this perspective, there are two views, by which the banks have to be seen: banks as intermediary and banks as multinational companies with interest in reduction of their tax liabilities. Banks can be assistants for their clients when it comes to the tax avoidance but there are differences between their attitudes to clients with tax avoidance tendencies. Clients of banks mainly accents financial secrecy, in which Switzerland is consider being one of the best. Banks’ tax avoidance is different problem and there are also differences between them in this case. Countries, which are magnet in their profit shifting schemes, are Luxembourg or Ireland in EU and some of the Caribbean islands. Clients and banks prefer different countries in their tax planning activities and this is caused by their different needs. On the one hand, clients appreciate secrecy, on the other hand, banks’ profit shifting process does not require it at the first place and they can focus on reducing of their tax costs or changing location for investment purposes.
Finanční sektor a jeho role v rámci mezinárodního daňového plánování
Keywords: Tax Planning; Financial Sector; Tax Havens; Daňové plánování; Finanční sektor; Daňové ráje